The correlation between creativity and learning styles with quran memorization achievement among 5c grade female students at salafiyah ula - Ahmad Fadlur Rahman Bayuny; Amalia Sabila; Maskur; Inas Umniyah; Inayatul Farihah; Belina Hendri Saputri (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2025)
This research aims to determine the relationship between the level of creativity and learning style on the achievement of memorizing the Al-Quran in class 5C students at the Salafiyah Ula Islamic Center Bin Baz Yogyakarta in the 2023/2024 academic year. The subjects of this research were students of class 5C Salafiyah Ula Putri Islamic Center Bin Baz, with a total sample of 20 students. The sampling technique used in this research is a saturated sampling technique. The measuring instruments used are the creativity level scale and the learning style scale. Data were analyzed using Pearson product moment and multiple correlation tests. The level of correlation coefficient between the variables of creativity level and learning style on Al-Quran memorization achievement shows an F change of 0.808 > 0.05, so it can be concluded that the variables of creativity level ( ) and learning style ( ) do not have a significant relationship with the memorization achievement variable. Al-Quran (Y) simultaneously The results of the hypothesis test based on the T test results table on variable The results of the hypothesis test based on the T test results table on variable The results of the correlation between the three variables are 25% and the remaining 75% is distributed by other variables.